ANALISIS PENGARUH TINGKAT PREDIKSI FINANCIAL DISTRESS TERHADAP IMBAL HASIL SAHAM PADA SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Priyo Purnomo (Universitas Mercu Buana, 2014)
Abstract. This study aims to examine and analyze the effect of Z-Score value tothe stock returns of the mining companies listed in IDX for period of 2009-2013.The research design used in this study is quantitative approach. From apopulation of 37 mining companies, only 33 companies selected as the samplewith purposive sampling method (non probability sample). The method ofanalysis used in this study is panel data regression using Eviews version 8statistics software. The research will conducted in descriptive analysis throughAltman Z-score method. Based on the Z-score it will be analyzed the impact to thereturn of each stock. The results show that generally the stock return is influencedby the Z-Score value. The higher the Z-Score, the more valuable the stock return.Mining sector listed in IDX generally in the „grey area‟. To prevent loss, investorsuggested to invest only in the „safe zone‟ stocks.Keywords: Altman Z-Score,bankruptcy, stock return, mining, panel dataregression